Self-knotting of infant feeding tube in urethra in male child an unfortunate complication-case report - Bijay Kumar Suman; Ram Jeewan Singh; Keerthana Bachala; Amit Kumar Sinha (International Journal of Contemporary Pediatrics, 2023)
Urethral catheterisation is a common routine procedure. Knotting of infant feeding tube in genitourinary tract is a rare complication. Various methods have been used in the removal of a knotted catheter. The methods include gentle but sustained traction under general anaesthesia, open cystostomy and endoscopic retrieval.